THE PRINCIPLES OF OPTIMIZATION OF LOGISTICS SERVICES OF PRODUCT DELIVERY IN THE AGRICULTURAL COMPLEX (Proceedings of International Educators Conference, 2022)
The theoretical and legal basis of agricultural logistics and its prospects are analyzed in the article. Information is provided on the formation of a logistics complex system and its possibilities to ensure effective supply chains of agricultural products.